Caracterização do transporte de sedimentos em pequeno rio urbano na cidade de Santa Maria-RS - Scapin, Juliana (2005)
This paper presents the results of the sediment transport assessment in a small urban stream in Santa Maria city, RS. Liquid and solids discharges were measured and the bed material was collected during thirteen raining events, between December 2003 and November 2004. The laboratory tasks included the particle size analyses and the sediment concentration. The obtained data were used to evaluate the efficiency of the following methods: Einstein Modified by Colby and Hembree (1955), Colby (1957), Engelund and Hansen (1967), Yang (1973), Ackers and White (1973), Van Rijn (1984), Karim (1998) and Cheng (2002). It was done to estimate the solid discharge at the considered measurement section. Einstein Modified by Colby and Hembree (1955) and Colby (1957) are the methods that include measured data of the suspended sediment concentration and are the ones that presented the best results, they presented ratios between the calculated and measured discharge of 1.01 and 1.33 and dispersion index of 0.11 and 0.44, respectively. Considering the total sediment discharges indirect estimative methods, Yang was the one that presented the best results with ratios between the calculated and measured discharges of 1.41 and dispersion index of 2.23. Karim (1998) and Ackers and White (1973) presented satisfactory results, with ratios between the calculated and measured discharges of 0.65 and 0.59 and dispersion indexes of 3.06 and 3.20, respectively. Van Rijn (1984) method presented a ratio between the calculated and measured discharge of 3.53 and dispersion index of 9.37. The worst results were presented by Engelund and Hansen (1967) and Cheng (2002) methods with ratios between the calculated and measured discharges of 4.35 and 24.22 and dispersion indexes of 15.38 and 562.26, respectively.